Direct Synthesis of Sodalite from Indonesian Kaolin for Adsorption of Pb2+ Solution, Kinetics, and Isotherm Approach - Tri Wahyuni; Didik Prasetyoko; Suprapto Suprapto; Imroatul Qoniah; Hasliza Bahruji; Ahmad Anwarud Dawam; Sugeng Triwahyono; Aishah Abdul Jalil (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
Indonesian kaolin was used as precursor for synthesis of sodalite. Synthesis parameters were optimized by varying the Si/Al ratios, stirring and aging conditions, and water composition. X-ray diffraction (XRD), Fourier Transform Infra Red (FTIR), Scanning Electron Microscope-Energy Dispersive Xray (SEM-EDX), and Particle Size Analyzer (PSA) were used to characterize sodalite. The potential of sodalite as adsorbent for heavy metal Pb2+ ions removal from waste water was investigated in this work. The uptake adsorption capacities of sodalite was 90-100 mg/g from synthesized sodalite crystallized for 24 and 48 hours, and commercial silica. The kinetic of Pb2+ adsorption was a pseudo second order reaction and the adsorption coefficients was followed Langmuir adsorption isotherm.